PENEGAKAN HUKUM TERHADAP PENJUALAN PAKAIAN BEKAS IMPOR DI KOTA SIDIKALANG KABUPATEN DAIRI SUMATERA UTARA - Doni Novrian Kudadiri; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Export-Import including in economic activities or actions that are usefulfor advancing the economy of a country, many parties are involved and bothbenefit, both profits from sales and profits from fulfilling needs. Remember thatuse clothes import used very potentially endanger health and body Publicespecially consumer clothes used import so that no safe for used and utilized byconsumers , on the other hand clothes used import could hinder growth industrytextiles in country , then government Secrete regulation about ban import clothesused by Minister Trading through Regulation Minister Trading Republic ofIndonesia Number 51/M-DAG/PER/7/2015 Concerning Ban Import Clothes Used, in Article 2 mentions “ clothes used prohibited for imported to in territory of theUnitary State Republic of Indonesia”.Purpose conducted study this namely: First, for know implementationenforcement law to sale clothes used import . Second, know obstacle inenforcement law to sale clothes used import . Third, knowing efforts made _ forresolve obstacle in enforcement law sale clothes used import . Type study lawused _ writer is type study law sociological . Study sociological this is typereviewed research _ from legal purposeResults from the research conducted is that Law Enforcement AgainstImported Used Clothing Traders in Sidikalang City so far has only beensocialized to imported used clothing traders by the Department of Industry andTrade of Dairi City without following up on these used clothing traders, theobstacles experienced in carrying out law enforcement are the absence of CivilServant Investigators, the lack of awareness and concern for the communitytowards the law, the trade of imported used clothing has become entrenched, andthe geographical location of the city of Sidikalang. Author 's Suggestion , Firstvery need exists efforts to socialize not only to traders of imported used clothingbut also to the general public about the dangers and the resulting impacts useclothes used . Second, PPNS is very needed for coordinate with apparatusenforcer law others related trading clothes used the so that could followed up inthe legal process in force . Third, necessary exists something supervising agency _trading clothes used created imports _ by government area local so that Thingthis can zoom out circulation sale clothes used import .Keywords : Traders , Apparel Used Import , Socialization